Upaya Meningkatkan Hasil Belajar Menggambar Bentuk Buah Teknik Krayon - Nurul Cindy Paramita; Azmi Azmi; Adek Cerah Kurnia Azis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The purpose of this study was to improve the quality of images of children from those who did not know to understand the basic image of the fruit shape drawing by applying the drill method in coloring crayon media activities in class VI-A of SD Negeri No. 081232 Sibolga. Training Method is a method that can be used to convey subject matter or information through repeated forms of exercises so that students have dexterity or skills higher than what is learned. The research subjects totaled 29 students. This training method uses the Pre Test action, Cycle I, Cycle II, to improve student learning outcomes. Gradually in the pre-test action, researchers found the average value of learning percentage is still 52% followed by the first cycle found an average student learning is good at 86.7% and quite good at 13.3% in the sense that it has started well. Then further improved in the second cycle researchers found 89.66% very good and 10.34% good, it can be said that the improvement in student learning outcomes for the better and improved. Then the researchers decided not to continue the action on the activity of coloring pictures of fruit shapes. The application of the training method (drill) has been successfully carried out and can be a reference and a strategy for learning fine arts, especially drawing.